RESPONS PERTUMBUHAN DAN HASIL UBI JALAR UNGU (Ipomoea batatas L) PADA BERBAGAI PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK NPK MUTIARA - Eka Rahmawati; Kaharuddin Kaharuddin (Jurnal Magrobis, 2021)
This study aims to see the effect of chicken coop and NPK pearls on the growth and yield of purple sweet potato (Ipomoea batatasL). This study was started in August - November 2020, located on Ikip Mekarsari Street, Tenggarong District, Kutai Kartanegara Regency, East Kalimantan Province. The research was arranged in a factorial Randomized Complete Block Design (RCBD) consisting of 2 factors and repeated 3 times. The first factor is the provision of chicken manure (p) which consists of 3 levels, namely p0 (without treatment), p1 (20 t ha-1), p2 (40 t ha-1). And the second factor is the pearl NPK fertilizer (n) which consists of 3 levels, namely n0 (without treatment), n1 (300 Kg ha-1), n2 (600 Kg ha-1). The results showed that chicken manure had no significant effect on all observed parameters. The highest average yield of plants t ha-1 is the treatment p2 (40 t ha-1) 26,58 t ha-1. while for the lowest treatment with an average of 25,46 t ha-1, namely the p1 treatment (20 t ha-1). The results showed that NPK fertilizer had no significant effect on all observed parameters. The highest average yield of plants t ha-1 was at treatment n2 (600 Kg ha-1) 26,11 t ha-1, while for the lowest treatment with an average of 25,68 t ha-1, namely treatment n1 (300 Kg ) ha-1). The results of the interaction between chicken manure and NPK fertilizer did not significantly affect all parameters. The highest average yield of t ha-1 was the p2n2 treatment with a yield of 26,90 t ha-1. And the lowest average yield of t ha-1 is the p1n1 treatment with a yield of 24,73 t ha-1.